The MICA‐129 dimorphism affects NKG2D signaling and outcome of hematopoietic stem cell transplantation - Antje Isernhagen; Dörthe Malzahn; Elena Viktorova; Leslie Elsner; Sebastian Monecke; Frederike von Bonin; Markus Kilisch; Janne Marieke Wermuth; Neele Walther; Yesilda Balavarca; Christiane Stahl‐Hennig; Michael Engelke; et al. (EMBO Molecular Medicine)
Abstract The MHC class I chain‐related molecule A (MICA) is a highly polymorphic ligand for the activating natural killer (NK)‐cell receptor NKG2D. A single nucleotide polymorphism causes a valine to methionine exchange at position 129. Presence of a MICA‐129Met allele in patients (n = 452) undergoing hematopoietic stem cell transplantation (HSCT) increased the chance of overall survival (hazard ratio [HR] = 0.77, P = 0.0445) and reduced the risk to die due to acute graft‐versus‐host disease (aGVHD) (odds ratio [OR] = 0.57, P = 0.0400) although homozygous carriers had an increased risk to experience this complication (OR = 1.92, P = 0.0371). Overall survival of MICA‐129Val/Val genotype carriers was improved when treated with anti‐thymocyte globulin (HR = 0.54, P = 0.0166). Functionally, the MICA‐129Met isoform was characterized by stronger NKG2D signaling, triggering more NK‐cell cytotoxicity and interferon‐γ release, and faster co‐stimulation of CD8+ T cells. The MICA‐129Met variant also induced a faster and stronger down‐regulation of NKG2D on NK and CD8+ T cells than the MICA‐129Val isoform. The reduced cell surface expression of NKG2D in response to engagement by MICA‐129Met variants appeared to reduce the severity of aGVHD.